Att dela språk men inte samtalsmönster: återkoppling i sverigesvenska och finlandssvenska handledningssamtal - Marie Nelson; Sofie Henricson; Catrin Norrby; Camilla Wide; Jan Lindström; Jenny Nilsson (Föreningen för nordisk filologi, 2022)
In this article, we present a study of oral feedback (back-channels and responsive turns) given in academic counselling meetings between an essay supervisor and one or two students. The purpose of these meetings is to discuss and improve an academic text written by the students. Our data consist of naturally occurring Sweden-Swedish and Finland-Swedish institutional interactions at the university level. The overall aim of the study is to compare feedback patterns in the Sweden Swedish and the Finland-Swedish data and to contribute to the field of variational pragmatics. A detailed analysis of the recorded interactions reveals overt differences in the frequency, intensity and distribution of feedback in the two varieties of Swedish. In the Sweden-Swedish data, there is a preference for relational work, evidenced, for instance, by students praising the advice given by the supervisor. In the Finland-Swedish data, an orientation towards clarity is prominent and corrective advice, for instance, is usually uttered in a straightforward way. Our results support previous findings on communicative patterns in Sweden and Finland. These findings highlight the dialogic nature of institutional communication in Sweden, on the one hand, and the orientation to the task and its result in comparable situations in Finland, on the other. The outcome of this study adds to the understanding of the communicative patterns of Sweden- Swedish and Finland-Swedish with a detailed analysis of the oral feedback occurring in counselling meetings.